Association Between the Microsatellite Instability Status and the Efficacy of Postoperative Adjuvant Chemoradiotherapy in Patients With Gastric Cancer - Dai, Dongfang; Zhao, Xiaohui; Li, Xiaoqin; Shu, Yongqian; Shen, Bo; Chen, Xiaofeng; Chen, Deyu; Wang, Deqiang (Frontiers in Oncology, 2020)
Purpose: The effect of microsatellite instability (MSI) on the response to radiotherapy remains unknown. The aim of this study was to investigate the association between the MSI status and the outcomes of gastric cancer (GC) treated by surgical resection with or without postoperative adjuvant chemoradiotherapy. Methods: The records of patients who underwent surgical resection of stage IB–III GC with or without postoperative adjuvant chemoradiotherapy were retrospectively retrieved from the Affiliated Hospital of Jiangsu University (n = 89), The Cancer Genome Atlas (n = 202), and the Asian Cancer Research Group (n = 138). The primary endpoint was overall survival (OS). Results: The MSI status had no significant influence on OS in all cohorts. Compared with surgery alone, adjuvant chemoradiotherapy improved or tended to improve OS of patients with stage III disease, irrespective of the MSI status, in all cohorts. Among patients with stage Ib/II disease, only those with microsatellite stability (MSS) benefited from chemoradiotherapy in terms of OS, whereas those with MSI showed no improvement in OS. A comparison of gene expression profiles between MSI stage Ib/II GC and MSS stage Ib/II GC revealed that MSI correlated with the overexpression of thymidylate synthetase, a marker of fluoropyrimidine resistance. Furthermore, tumor hypoxia scoring for stage Ib/II lesions showed significantly greater hypoxia in MSI tumors than in MSS tumors. Conclusions: The findings of this study suggest that postoperative adjuvant chemoradiotherapy is effective for stage III GC, regardless of the MSI status. However, MSI may predict a poor response to postoperative adjuvant chemoradiotherapy in patients with stage Ib/II GC.